Teaching Anxiety Experienced by Indonesian Student Teachers of Multidisciplinary Education Study Program - Vina Agustiana; Nunu Nurhayati (ELT in Focus, 2019)
With the demands of professionals, the study reports that there is a great deal of anxiety that arises in real teaching. As an effort to reduce the teaching anxiety, this study explores the level of teaching anxiety faced by student teachers in implementing real teaching as well as factors that can trigger the emergence of anxiety. This research was conducted quantitatively by applying the survey as the research strategy. The Student Teacher Anxiety Scale (STAS) found by Hart (1987) became a research instrument with language modification performed. 238 student teachers of Multidiciplinary Education Study Program (ESP) at one of the Private University in Indonesia who will carry out real teaching are involved as research respondents. The respondents consist of 6 different ESP. Based on the results of the study, it can be seen that the level of teaching anxiety faced by student teachers of multidiciplinary ESP in carrying out real teaching activities is at a high level with an average of 3.69. The level of anxiety experienced by student teachers of each ESP are as follows: Primary School Teacher (3.89), Mathematics (3.74), English Language (3.48), Indonesian Language (3.47) are at a high level. While the level of teaching anxiety of student teachers of Biology ESP (3.35) and Economic ESP (3.26) are at the normal level. Meanwhile, the most influencing factor causing the teaching anxiety were teaching preparation (3.86), teaching evaluation (3.73), class control (3.71), school staff (3.58), and failure in teaching (3, 58). With the anxiety that arises, good communication is the initial solution that can be done so that real teaching activities get better. Finally, real teaching will be more useful when the anxiety that arises is considered as a stimulation so that students can carry out better real teaching activities.